"Fly ash and GGBFS based powder-activated geopolymer binders: A viable sustainable alternative of portland cement in concrete industry". (December 2016) - Neupane, Kamal
Highlights: Powder-activated geopolymer binder can be mixed and handled as conventional Portland cement. Geopolymer concrete can be set and harden in ambient curing conditions. Geopolymer concrete possess higher tensile and flexural strength than OPC concrete of same grade. Geopolymer concrete possess similar modulus elasticity to OPC concrete of same grade and can be estimated usingAustralian Standard 3600 (2009) Geopolymer concrete possess similar drying shrinkage to OPC concrete of same grade at ambient temperature curing. Abstract: Geopolymer is a new binding material, synthesized by alkali activation of aluminosilicate compounds. Previous researches around the world postulated that concrete from geopolymer binder exhibited superior engineering, thermal and durability properties than ordinary Portland cement (OPC) concrete, such as higher mechanical strengths, higher resistivity to sulphate and acid attacks and higher thermal resistivity. Geopolymers are generally made from activation of aluminosilicate powders by highly concentrated sodium hydroxide and or sodium silicate solutions, known as liquid-activated geopolymer. Recently, some cement and concrete companies around the world have commenced the production of liquid activator based geopolymer binders. However, this type of geopolymer does not appear as a viable replacement of Portland cement in concrete industry despite its substantial environmental benefits because of its limitation in mixing and handling process. Powder-activated geopolymer contains alkali activators in powder form which are blended together with source material. This geopolymer binder is physically similar to OPC and mixing and handling process are also similar to conventional process. Experimental results showed that concrete from this binder can set and harden in ambient temperature with significant early age strength. Two types of powder-activated geopolymer binders having different proportions of fly ash and slag were used in this study. Engineering properties of geopolymer concrete of four different strength grades (40, 50, 65 and 80 MPa) were investigated in detail at ambient curing condition and compared with OPC concrete of same grade.